Efektivitas Filtrat Daun Cengkih (Syzygium aromaticum) sebagai Repellent terhadap Lalat Rumah (Musca domestica) dengan Metode Space Spraying - Ilmiaty Rosillah; Ngadino Ngadino; Ferry Kriswandana (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
The house fly is a mechanical vector for spreading diseases. Controlling flies using chemical repellents continuously could results in resistance to flies. The other alternative is using clove leave filtrate as a natural repellent. The content of clove leaves that have function as a repellent are: eugenol, saponins, and flavonoids. The purpose of this study was to analyze the effectiveness of clove leaf filtrate as a natural repellent against house flies. The space spraying method was carried out with an air diffuser and exposed for 6 hours. This type of research uses a simple quasi-experiment with a post test only control group design. The study used clove leaf concentrations of 10%, 15%, 20%, aquadest, and was replicated 6 times. The number of house flies used are 600. The result showed that the average flies that refused bait on the control was 28%, the concentration of 10% was 61.3%, 15% was 84%, and 20% was 91.3%. The results of the One Way Anova test, stated the p-value of 0.000 (<0.05), which means that there is a difference in the average number of house flies that refuse bait.The conclusion of this study is that clove leaf filtrate is effective as a house fly repellent.